Interactions between oxygen homeostasis, food availability, and hydrogen sulfide signaling - Iranon, Nicole N.; Miller, Dana L. (Frontiers in Genetics, 2012)
The ability to sense and respond to stressful conditions is essential to maintain organismal homeostasis. It has long been recognized that stress response factors that improve survival in changing conditions can also influence longevity. In this review, we discuss different strategies used by animals in response to decreased O2 (hypoxia) to maintain oxygen homeostasis, and consider interactions between hypoxia responses, nutritional status, and H2S signaling. O2 is an essential environmental nutrient for almost all metazoans as it plays a fundamental role in development and cellular metabolism. However, the physiological response(s) to hypoxia depend greatly on the amount of O2 available. Animals must sense declining O2 availability to coordinate fundamental metabolic and signaling pathways. It is not surprising that factors involved in the response to hypoxia are also involved in responding to other key environmental signals, particularly food availability. Recent studies in mammals have also shown that the small gaseous signaling molecule hydrogen sulfide (H2S) protects against cellular damage and death in hypoxia. These results suggests that H2S signaling also integrates with hypoxia response(s). Many of the signaling pathways that mediate the effects of hypoxia, food deprivation, and H2S signaling have also been implicated in the control of lifespan. Understanding how these pathways are coordinated therefore has the potential to reveal new cellular and organismal homeostatic mechanisms that contribute to longevity assurance in animals.